Modernization and the Japanese Factory - Marsh, Robert Mortimer; Mannari, Hiroshi, 1925- (Book collections on Project MUSE., 1976)
While some writers account for Japan's postwar economic ""miracle"" in terms of a distinctively Japanese, traditional model of social organization, the writers of this study consider Japan's technological growth to have been accompanied by convergence toward modernized social organization. The authors test both of these theoretical models. Their data are derived from a nine-month period of observation, analysis of company records, interviews of personnel, and questionnaire responses from production, staff, and managerial employees in three main Japanese firms. Other firms were visited more br.